CYBER HYGIENE PRACTICES AND PROVIDING PROPER EDUCATION - Подліняєва, Оксана; Ситник, Лариса (SWorldJournal, 2023)
The article discusses the essence of the concept of "cybersecurity" and the problems of solution. This area is related to the protection of: digital information, operating systems, computer networks, servers, databases, public and private institutions fro